Estrogen induces a demethylation at the 5' end region of the chicken vitellogenin gene. - Wilks, A F (1982)
The two isoschizomeric restriction endonucleases Msp I and Hpa II have been used to study changes in the methylation pattern of the vitellogenin gene after estrogen treatment. In the liver of the both estrogen-treated and nontreated chickens the vitellogenin gene is heavily methylated. However, estradiol causes a demethylation of a Hpa II site(s) at the 5' end region of the gene. The same Hpa II restriction site(s) is also unmethylated in the liver of egg laying hens but is methylated in the liver of roosters or in erythrocyte DNA. In the mature oviduct where no vitellogenin is synthesized but where several egg white proteins are under the control of estrogen, there is also a demethylation of the 5'end region of the vitellogenin gene. This demethylation does not precede the initiation of transcription of the gene but persists, and increases, even after vitellogenin transcription has ceased in the liver. Taken together, the results strongly suggest that in estrogen-responsive tissues the vitellogenin gene becomes demethylated at its 5' end region after estrogen stimulation whether the gene is expressed or not.